Effects of Electrical Current, pH, and Electrolyte Addition on Hydrogen Production by Water Electrolysis - Sri Haryati (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Hydrogen is viewed as one of the most potential energy source in the future. One of methods to produce hydrogen is by electrolysis of water. Variables that was applied in this work were electrical current (0.5 A and 0.9 A), pH (13.47 and 13.69), and electrolyte additions (namely NaOH and KOH) with processing times for 30 minutes. The result of this work were variations of electrical current at 0.9 A, pH at 13.69 and electrolyte NaOH is at 278.394 L with volume rate 154.663 mL/s produced most amount of hydrogen, whereas condition of 0.5 A, pH 13.47 and electrolyte KOH was 75.122 L with volume rate of 41.734 mL/s yielded the lowest amount.